2015
DOI: 10.1002/anie.201508232
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a “Masked” Terminal Nickel(II) Sulfide by Reductive Deprotection and its Reaction with Nitrous Oxide

Abstract: Addition of 1 equiv of KSCPh3 to [LRNiCl] (LR = {(2,6-iPr2C6H3)NC(R)}2CH, R = Me, tBu) in C6H6 results in the formation of [LRNi(SCPh3)] (1, R = Me; 2, R = tBu) in good yields. Subsequent reduction of 1 and 2 with 2 equiv of KC8, in cold (-25 °C) Et2O, in the presence of 2 equiv of 18-crown-6, results in the formation of “masked” terminal NiII sulfides, [K(18-crown-6)][LRNi(S)] (3, R = Me; 4, R = tBu), also in good yields. An X-ray crystallographic analysis of these complexes suggests that they feature partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 53 publications
4
53
0
Order By: Relevance
“…We recently reported the synthesis of an Ni II [23][24][25] resulting in our classification of this complex as a "masked" terminal sulfide. Importantly, however, the presence of the coordinating [K(18-crown-6)] + cation likely tempers the reactivity of the sulfide ligand, and possibly limits the extent of reactivity of this functional group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported the synthesis of an Ni II [23][24][25] resulting in our classification of this complex as a "masked" terminal sulfide. Importantly, however, the presence of the coordinating [K(18-crown-6)] + cation likely tempers the reactivity of the sulfide ligand, and possibly limits the extent of reactivity of this functional group.…”
Section: Introductionmentioning
confidence: 99%
“…The Ni-S and C-S bond lengths of 2.181(2) Å and 1.870(7) Å, respectively, are both consistent with single bonds. 23,26 For comparison, the Ni-S bond length in the starting material is markedly shorter (2.0869(1) Å). 23 The Ni-N bond lengths in 1 (1.901 (4) Figure S6), which is also consistent with the proposed mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These complexes have proven to react with a variety of small molecules, including CS 2 and N 2 O. 10,11 Given its potent reactivity, we hypothesized that…”
mentioning
confidence: 99%
“…[35] Interestingly,t he direct addition of N 2 Ot o an isolated metal-oxo species has not been developed as as ynthetic route to this ligand. [36] In conclusion, we have demonstrated that the aluminyl anion [Al(NON Ar )] À reacts with two abundant greenhouse gases under mild conditions to generate innocuous and potentially useful chemical products.B oth reactions proceed through cycloaddition to an intermediate monoalumoxane anion, which has been isolated as the potassium salt. [36] In conclusion, we have demonstrated that the aluminyl anion [Al(NON Ar )] À reacts with two abundant greenhouse gases under mild conditions to generate innocuous and potentially useful chemical products.B oth reactions proceed through cycloaddition to an intermediate monoalumoxane anion, which has been isolated as the potassium salt.…”
Section: Methodsmentioning
confidence: 99%